The More Doctors Program and the rearrangement of medical residency education focused on Family and Community Medicine - Felipe Proenço de Oliveira; Cássia de Andrade Araújo; Odete Messa Torres; Alexandre Medeiros de Figueiredo; Priscilla Azevedo Souza; Francisco Arsego de Oliveira; Maria Martins Alessio (Faculdade de Medicina de Botucatu (Unesp), 2019)
Abstract The More Doctors Program (PMM) was created in 2013 to address problems such as the insufficient number and unequal distribution of doctors, and their inadequate education profile to fulfill the population needs. Among other axes, it proposes changes in medical education, including the rearrangement and expansion of residency, suggesting one seat for every medical course graduate. This study reflects upon the elements that were essential to propose and implement changes in medical residency through PMM. The following advances were identified: better distribution of residency seats across Brazil; diversification of universalization strategies; regulations for residency seats focused on Family and Community Medicine; and preceptorship qualification. The conclusion section presents the challenges faced by the required institutional effort to maintain PMM's actions in order to regulate residency and expand actions to other professions.